2019
DOI: 10.32511/tourism.v2i1.316
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Daya Tarik Wisata Dan Aksesibilitas Terhadap Tingkat Kunjungan Wisata Ke Desa Boti Kabupaten Timor Tengah Selatan

Abstract: Studi dalam penelitian ini mengenai pengaruh daya tarik wisata dan aksesibilitas terhadpa tingkat kunjungan wisata ke Desa Boti. Masalah yang diangkat dalam penelitian ini yaitu :  (1) apakah daya tarik wisata mempengaruhi tingkat kunjungan wisata ke Desa Boti, (2) apakah aksesibilitas mempengaruhi tingkat kunjungan wisata ke desa Boti. Penelitian ini menggunakan pendekatan analisis deskriptif kualitatif, data-data yang dikumpulkan dalam penelitian ini dikumpulkan dalam kondisi yang asli dan alamiah. Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Findings of Abdulhaji, &Sina Hi (2016) also found that access affects tourism activity. Kabu (2019) states that access to tourism is essential in its role and influence on tourism activities. Besides, Edwin, Wibowo, &Shihab (2018) also found that access such as information and other facilities, directly and indirectly, impacted tourism development.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of Abdulhaji, &Sina Hi (2016) also found that access affects tourism activity. Kabu (2019) states that access to tourism is essential in its role and influence on tourism activities. Besides, Edwin, Wibowo, &Shihab (2018) also found that access such as information and other facilities, directly and indirectly, impacted tourism development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are three important aspects of tourism products that must be considered by tourists, namely tourist attraction (tourist attractions), ease of access to reach tourist destinations (accessibility), and facilities available at tourist attractions (amenities). In addition to facilities and several other variables, tourist attraction also plays an important role in determining tourists' interest in visiting a destination again (Basiya & Rozak, 2012;Djunaid, 2020;Kabu, 2019;Lapian et al, 2015;Nurbaeti et al, 2021). In addition to this, empirical studies also prove the effect of tourist attraction on satisfaction (Herman, 2021;Junaida, 2019) and tourist loyalty (Basiya & Rozak, 2012).…”
Section: Tourism Attractionsmentioning
confidence: 99%
“…Pengembangan pariwisata yang ada dimadura dapat dilakukan dengan penyusunan paket wisata keliling madura. Paket wisata sendiri merupakan sebuah perjalanan wisata yang dibuat dari beberapa tujuan kunjungan dimana dijual dalam satu kesatuan harga (Kabu & Misa, 2022). Penyusunan ini sesuai dengan slogan visit madura, dimana dengan adanya paket wisata membuat para wisatawan dengan mudah menikmati seluruh wisata yang ada di Madura secara terorganisir.…”
unclassified